Advanced Biophotonics Techniques: The Role of Optical Tweezers for Cells and Molecules Manipulation Associated With Cancer - Spyratou, Ellas (Frontiers in Physics, 2022)
Rapid advances in Biophotonics are revolutionizing the illumination of several diseases and, among them, the monitoring of cancer pathogenesis and therapy. Today, several efforts aim to miniaturize the Biophotonics tools, leading to the namely Nanobiophotonics. This scientific field refer to the development of novel technologies, biosensors, and drug delivery systems for prevention, diagnosis, and treatment of diseases at the nanoscale, in sub-cellular and molecular level. Modern non-invasive laser-based techniques are applied in different domains, from practical, clinical applications to molecular and cellular biology fundamental research. Among the plethora of photon-based techniques, optical trapping is a very promising tool for improving the understanding of cancer at cellular level. Recently, optical tweezers are revived as a potential technique for cell characterization, tracking cells behavior and probing interactions forces between cells, cells-biomolecules, and cells-nanoparticles. In this review, we aim to exhibit the state-of the art advances of Biophotonics in the diagnostic and therapeutic field of cancer focusing on the role of optical tweezers.